The CD28-B7 Family in Anti-Tumor Immunity: Emerging Concepts in Cancer Immunotherapy - Leung, Joanne; Suh, Woong-Kyung (Immune network, 2014)
The interactions between B7 molecules and CD28-family receptors are crucial in the regulation of adaptive cellular immunity. In cancer, the aberrant expression of co-inhibitory B7 molecules has been attributed to reduced anti-tumor immunity and cancer immune evasion, prompting the development of cancer therapeutics that can restore T cell function. Murine tumor models have provided significant support for the targeting of multiple immune checkpoints involving CTLA-4, PD-1, ICOS, B7-H3 and B7-H4 during tumor growth, and clinical studies investigating the therapeutic effects of CTLA-4 and PD-1 blockade have shown exceptionally promising results in patients with advanced melanoma and other cancers. The expression pattern of co-inhibitory B7 ligands in the tumor microenvironment has also been largely correlated with poor patient prognosis, and recent evidence suggests that the presence of several B7 molecules may predict the responsiveness of immunotherapies that rely on pre-existing tumor-associated immune responses. While monotherapies blocking T cell co-inhibition have beneficial effects in reducing tumor burden, combinatorial immunotherapy targeting multiple immune checkpoints involved in various stages of the anti-tumor response has led to the most substantial impact on tumor reduction. In this review, we will examine the contributions of B7- and CD28-family members in the context of cancer development, and discuss the implications of current human findings in cancer immunotherapy.